Driving Consumer Purchasing Decisions in MSME Souvenir Retail: A Case Study of Toko Jongko Waiti - Pipih Sopiyan; Deni Istiono; Siti Julaeha (Finance and Business Management Journal, 2026)
This study investigates the determinants of consumer purchasing decisions in the souvenir retail sector, focusing on Toko Oleh-oleh Jongko Waiti. Despite shifting market dynamics, the establishment has maintained robust sales over the past three years, signaling strong customer buying interest. This research aims to empirically analyze the individual and simultaneous effects of pricing strategies and product assortment (completeness) on consumer purchasing decisions. Utilizing a descriptive-verificative approach, data were gathered via a survey questionnaire from a sample of 100 respondents, selected through an accidental sampling technique. Data analysis was executed using multiple linear regression, supplemented by classical assumption tests, F and t-tests, and the coefficient of determination). The empirical findings indicate that pricing strategies exert a positive and statistically significant influence on purchasing decisions. Concurrently, product assortment also significantly and positively affects consumer choices. Simultaneously, both predictors serve as robust determinants of purchasing decisions. These insights underscore the imperative for retail managers to optimize pricing fairness and expand product variety to sustain competitive advantage.